Periodontal pathogens and their association with incident all‐cause and Alzheimer's disease dementia in a large national survey: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Beydoun, May A; Beydoun, Hind A; Hossain, Sharmin A; El‐Hajj, Ziad W; Weiss, Jordan; Zonderman, Alan
Abstract: Background: Infectious agents including periodontal pathogens have recently appeared as important actors in Alzheimer's Disease (AD) pathology. We examined associations of serum immunoglobulin G (IgG) against periodontal pathogens and Pd markers with incident all‐cause and AD dementia as well as AD mortality among U.S. middle‐aged and older adults. Method: Periodontal disease (Pd) markers [Clinical Attachment Loss (CAL); probing depth and periodontal pathogen immunoglobulin G (IgG)] were investigated in relation to AD and all‐cause dementia incidence and to AD mortality, using data from the third National Health and Nutrition Examination Surveys (NHANES III, 1988‐1994) linked longitudinally with National Death Index and Medicare data through January 1 st, 2014, with up to 26y of follow‐up. Sex‐ and age group‐specific multivariable‐adjusted Cox proportional hazards models were conducted. Result: Among those ≥65y, AD incidence and mortality were consistently associated with probing depth, two factors and one cluster comprised of IgG titers against Porphyromonas gingivalis ( Pg ), Prevotella melaninogenica ( Pm ) and Campylobacter rectus ( Cr ) among others. Specifically, AD incidence was linked to a composite of Cr and Pg titers (per SD, aHR=1.22; 95% CI, 1.04‐1.43, P=0.012), while AD mortality risk was increased with another composite (per SD, aHR=1.46; 95% CI, 1.09‐1.96, P=0.017) loading highly on Pg, Prevotella intermedia, Prevotella nigrescens, Fusobacterium nucleatum, Cr, Streptococcus intermedius, Capnocylophaga Ochracea and Pm . Conclusion: This study provides evidence for an association between periodontal pathogens and AD, which was stronger for older adults. Effectiveness of periodontal pathogen treatment on reducing sequelae of neurodegeneration should be tested in randomized controlled trials.